2005
DOI: 10.1038/sj.jhh.1001845
|View full text |Cite
|
Sign up to set email alerts
|

Lowering of blood pressure leads to decreased circulating interleukin-6 in hypertensive subjects

Abstract: Interleukin-6 (IL-6), the major proinflammatory cytokine, has been described to be associated with the hypertensive and atherosclerotic states. We aimed to explore whether the concentration of circulating IL-6 and adhesion molecules could be modified by decreasing blood pressure in hypertensive subjects. A total of 30 subjects (18 men), aged 34-48 years, were enrolled in this study, 17 hypertensive never-treated patients (HTA) and 13 normotensive subjects (C). HTA subjects were treated with irbesartan, 150-300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 25 publications
1
39
0
1
Order By: Relevance
“…The blocking of Ang II activity by angiotensin converting enzyme inhibitors or Ang II type 1 (AT1) receptor antagonists has been shown to result in anti-inflammatory effects and prevent or reduce the development of atherosclerosis in animal models. In humans, the anti-inflammatory effects of these agents have been suggested by a study of Vazquez-Oliva et al, which showed that treatment with the AT1 receptor antagonist irbesartan decreased blood pressure in hypertensive patients in parallel with an decrease in serum interleukin (IL)-6 to levels similar to those in normotensive individuals (17). Sanada et al reported that the elevation of serum soluble E-and Pselectin in patients with hypertension is preserved by benidipine, a long-acting calcium channel blocker (18).…”
Section: Introductionmentioning
confidence: 99%
“…The blocking of Ang II activity by angiotensin converting enzyme inhibitors or Ang II type 1 (AT1) receptor antagonists has been shown to result in anti-inflammatory effects and prevent or reduce the development of atherosclerosis in animal models. In humans, the anti-inflammatory effects of these agents have been suggested by a study of Vazquez-Oliva et al, which showed that treatment with the AT1 receptor antagonist irbesartan decreased blood pressure in hypertensive patients in parallel with an decrease in serum interleukin (IL)-6 to levels similar to those in normotensive individuals (17). Sanada et al reported that the elevation of serum soluble E-and Pselectin in patients with hypertension is preserved by benidipine, a long-acting calcium channel blocker (18).…”
Section: Introductionmentioning
confidence: 99%
“…Vazquez-Oliva et al (18) have shown that irbesartan treatment decreased the interleukin-6 level owing to its antiinflammatory effect in humans through the blocking of Ang II activity by Ang II type 1 (AT1) receptor antagonists. Angiotensin II type 1 receptor blockers (ARB), such as telmisartan, widely used for the treatment of hypertension to prevent organ damage such as renal and cardiac remodeling, are provided to obtain the benefits of selectively blocking Ang II at the level of the AT1 receptor.…”
mentioning
confidence: 99%
“…Plasma levels of IL-6 are strongly associated with hypertension in humans and can be decreased by administration of Ang II receptor antagonists. [1][2][3][4][5][6] In animal models of hypertension and volume overload-induced hypertrophy, IL-6 and its related cytokines, leukemia-inhibitory factor and cardiotrophin-1, are elevated. [7][8][9][10] In addition, Ang II can increase IL-6 synthesis in cultured cells via extracellular signal-regulated kinase, mitogenactivated protein kinase, and cAMP response elementbinding protein.…”
mentioning
confidence: 99%